On Orthogonal Coupled Fixed Point Results with an Application. (14th June 2022) - Mani, Gunaseelan; Gnanaprakasam, Arul Joseph; Javed, Khalil; Kumar, Santosh
Abstract : In this manuscript, owing to the concept of orthogonal coupled contraction mappings type I and II, we prove coupled fixed point theorem in orthogonal metric spaces. In order to strengthen our main results, a suitable example is presented. Moreover, the results we obtained supplement and improve previous research findings. A fruitful application is also supplied to endorse our outcomes.